HUBUNGAN PENGGUNAAN LENSA KONTAK DENGAN KEJADIAN BLEFARITIS Â PADA MAHASISWA KEBIDANANSTIKES BINA SEHAT PPNI MOJOKERTO - Indatul Laili, Siti; Nismawati, (JURNAL KEPERAWATAN BINA SEHAT, 2016)
A contact lens is a lens that attaches to the eye or the cornea used a person with impaired vision to improve eyesight. The use of contact lenses can lead blefaritis which is a severe inflammation of the eyelid are usually especially at the edges of the petals and the base of the eyelashes can be easily communicable and non communicable.The purpose of this research was to knowing relationship use of contact lenses with events blefaritis on midwifery students of STIKes Bina Sehat PPNI Mojokerto. The research design used cross sectional. The population in this research are all midwifery students of two and four semester STIKes Bina Sehat PPNI Mojokerto use contact lenses a number of 30 respondents. The sampel was all midwifery students of two and four semester STIKes Bina Sehat PPNI Mojokerto use contact lenses with total sampling teckhnic. The instrument in this research used interview. The time of this research 1-4 June 2015. Analyzing data used was cross tabel frekuensi distribution.The results showed that nearly half of respondents 12 respondents (40%) experiencing moderate blefaritis. This shows use of contact lenses can lead blefaritis, students feel like get smth in the eye, tears in her eyes, and feel the itch when using contact lenses.Keyword:Contact lens, blefaritis